Hybrid System Prediction for the Stock Market: The Case of Transitional Markets - Ralević, Nebojša M.; Glišović, Nataša S.; Đaković, Vladimir Đ.; Anđelić, Goran B. (Industrija, 2017)
The subject of this paper is the creation and testing of an enhanced fuzzy neural network backpropagation model for the prediction of stock market indexes, including the comparison with the traditional neural network backpropagation model. The objective of the research is to gather information concerning the possibilities of using the enhanced fuzzy neural network backpropagation model for the prediction of stock market indexes focusing on transitional markets. The methodology used involves the integration of fuzzified weights into the neural network. The research results will be beneficial both for the broader investment community and the academia, in terms of the application of the enhanced model in the investment decision-making, as well as in improving the knowledge in this subject matter.
Keywords: Investments; Prediction; Hybrid System; Stock; Neural networks; Market